nn - Dajović, Goran (Glasnik Advokatske komore Vojvodine, 2024)
The article tries to shed light on the possible benefit of some of the insigts, as well as the method of the philosophy of law for legal practice. In this sense, the characteristics of the philosophy of law, as a discipline and then three of its perspectives, which can be of importance to legal practitioners, are firstly presented. Then, in the light of those perspectives, a recent case from the practice of domestic misdemeanor courts is analyzed in detail. After the analysis undertaken, it is concluded that the general deficits in the judicial and legal system of Serbia do not favor the influence of legal philosophical insigts and methods in legal practice. However, this does not mean that they should not occupy a significant place in that practice. Moreover, it seems that they can significantly contribute to its fundamental change and the removal of its most serious defects.
Keywords: philosophy of law, argumentation, civil disobedience, practical reasonableness